'A thousand times more interesting': introducing the optical lantern into the Belgian classroom, 1880–1920. Issue 6 (2nd November 2021) - Egelmeers, Wouter; Teughels, Nelleke
ABSTRACT: In the early 1880s, Belgian educators were confronted for the first time with calls for the use of the optical lantern in schools. Around the same time, new pedagogical theories gained ground, which argued in favour of visually aided, more experiential forms of teaching. By investigating the pedagogical discourse on the introduction and use of image projection in Belgian primary and secondary schools between 1880 and 1920, this study investigates how campaigns for the educational use of lantern slides framed the optical lantern as an educational medium and to what extent this discourse was influenced by contemporary pedagogical theories. As such, this study sheds new light on the professional pressures placed on teachers and the expectations of how they should use media, and how these demands were often at odds with teachers' practical pedagogy.